Dinamika Identitas Nasional dalam Era Globalisasi - Saefulloh, Febri; Nadhia Alfia Tsurayya (Amal Insani Foundation, 2024)
In the era of globalization, many technological and informational advancements present opportunities to advance and prosper society. The development of technology and information offers numerous benefits in various fields such as technology, transportation, health, and others. Nonetheless, globalization also brings negative implications. One of these negative impacts is the influence of foreign cultures. The negative impact of globalization poses a challenge for the young generation in Indonesia to sustain their national identity. To address this challenge, it is crucial to reorient the national identity toward the younger generation. This reintroduction is necessary to preserve the national identity for inheritance to future generations